Following the moment 1990-1992: “And violence and disorder created Fujimori . . .” - Pedraglio, Santiago (2018)
This article focuses on the 1990 elections, in the context of an acute economical and political crisis that allowed an unknown, Alberto Fujimori, the victory over Mario Vargas Llosa. After this electoral period, the state of exception —configured gradually during the decade of 1980 by the actions of the Shining Path, the constitution of paramilitary commandos and the generalized economic and political crisis— entered into a new context. Fujimori changed his political discourse and initiated the organization of a broad conservative coalition around a neoliberal project.